Peculiarities of Phase Formation in Mn-Based Na SuperIonic Conductor (NaSICon) Systems: The Case of Na1+2 xMnxTi2- x(PO4)3(0.0 ≤ x ≤ 1.5) - Snarskis, Gustautas; Pilipavičius, Jurgis; Gryaznov, Denis; Mikoliū Naitė, Lina; Vilčiauskas, Linas (American Chemical Society, 2021)
NAtrium SuperIonic CONductor (NASICON) structured phosphate framework compounds are attracting a great deal of interest as suitable electrode materials for "rocking chair"type batteries. Manganese-based electrode materials are among the most favored due to their superior stability, resource non-criticality, and high electrode potentials. Although a large share of research was devoted to Mn-based oxides for Li- and Na-ion batteries, the understanding of thermodynamics and phase formation in Mn-rich polyanions is still generally lacking. In this study, we investigate a bifunctional Na-ion battery electrode system based on NASICON-structured Na1+2xMnxTi2-x(PO4)3 (0.0 ≤ x ≤ 1.5). In order to analyze the thermodynamic and phase formation properties, we construct a composition-temperature phase diagram using a computational sampling by density functional theory, cluster expansion, and semi-grand canonical Monte Carlo methods. The results indicate finite thermodynamic limits of possible Mn concentrations in this system, which are primarily determined by the phase separation into stoichiometric Na3MnTi(PO4)3 (x = 1.0) and NaTi2(PO4)3 for x < 1.0 or NaMnPO4 for x > 1.0. The theoretical predictions are corroborated by experiments obtained using X-ray diffraction and Raman spectroscopy on solid-state and sol-gel prepared samples. The results confirm that this system does not show a solid solution type behavior but phase-separates into thermodynamically more stable sodium ordered monoclinic α-Na3MnTi(PO4)3 (space group C2) and other phases. In addition to sodium ordering, the anti-bonding character of the Mn-O bond as compared to Ti-O is suggested as another important factor governing the stability of Mn-based NASICONs. We believe that these results will not only clarify some important questions regarding the thermodynamic properties of NASICON frameworks but will also be helpful for a more general understanding of polyanionic systems. ©
This project has received funding from the European Regional Development Fund (Project no. 01.2.2-LMT-K-718-02–0005) under grant agreement with the Research Council of Lithuania (LMTLT). We thank the High Performance Computing Center “HPC Saulėtekis” at the Faculty of Physics, Vilnius University, for the use of computational resources.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Diffraction; Electrodes; Energy; Materials; Transition metals